The Hindenburg [videorecording (DVD)] - Wise, Robert, 1914-2005; Levinson, Richard; Link, William; Gidding, Nelson; Scott, George C., 1927-1999; Bancroft, Anne, 1931-2005; Atherton, William; Thinnes, Roy; Young, Gig, 1913-1978; Meredith, Burgess, 1907-1997; Durning, Charles, 1923-2012; Dysart, Richard; et al. (MCA Home Video, 1998)
A dramatization of the journey and crash of the German dirigible, the Hindenburg.